Fragile X syndrome: genetic localisation by linkage mapping of two microsatellite repeats FRAXAC1 and FRAXAC2 which immediately flank the fragile site. Issue 12 (December 1991) - Richards, R I; Holman, K; Kozman, H; Kremer, E; Lynch, M; Pritchard, M; Yu, S; Mulley, J; Sutherland, G R
Abstract : We report the genetic localisation of the fragile site at Xq27.3 associated with fragile X syndrome. The position of the fragile site within the multipoint linkage map was determined using two polymorphic microsatellite AC repeat markers FRAXAC1 and FRAXAC2. These markers were physically located within 10 kilobases and on either side of the p(CCG)n repeat responsible for the fragile site. FRAXAC1 has five alleles with heterozygosity of 44% and is in strong linkage disequilibrium with FRAXAC2 which has eight alleles and a heterozygosity of 71%. No recombination was observed either between these markers in 40 normal CEPH pedigrees or with the fragile X in affected pedigrees. These markers provide the means for accurate diagnosis of the fragile X genotype in families by rapid polymerase chain reaction analysis and were used to position the fragile X within the multipoint map of the X chromosome to a position 3.7 cM distal to DXS297 and 1.2 cM proximal to DXS296.